(untitled) - Essien, Effiong (Cambridge, UK, 2003)
The book provides a concise and authoritative guide to manufacturing high-quality products for the consumer. It begins by considering issues of definition and the market trends. The book then discusses product formulation, key stages in production, good practice in safety and quality assurance, new product development and novel products
Keywords: Sausages